KAJIAN TENTANG “BEBAS NILAI” ILMU PENGETAHUAN DIPANDANG DARI SISI FILSAFAT ILMU DAN TEORI KUANTUM - Riyo - Samekto (Innofarm:Jurnal Inovasi Pertanian, 2010)
ABSTACTS The purpose of the article is to obtain understanding of how far is independence of science by philosophy of science and quantum theory point of view. From philosophy of science point of view, independence and objectivity of obtaining science is questionable because of acsiological, teteological, ethical aspects to support human needs. There is also evident in quantum physics theory supporting the subjectivity of the observers in examination during experiment. Subjectivity of obtaining science, therefore, must be intensively discuss in the field of metaphysics.